Photodynamic therapy review: principles, photosensitizers, applications, and future directions - Correia, J. H. (2022)
"Special issue in Honor of Dr. Michael Weber’s 70th Birthday: photodynamic therapy: rising star in pharmaceutical applications" is a reprint of articles from the Special Issue published online in the open access journal "Pharmaceutics" (ISSN 1999-4923), vol's 13, 14.